Effectiveness of The Guided Inquiry-Based Flipped Classroom Learning System on Buffer Solution Materials on Students’ Learning Outcomes - Megi Hartandi; Mawardi Mawardi (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
This study aims to reveal the effectiveness of the Guided Inquiry-based Flipped Classroom learning System on the buffer solution material on student learning outcomes. This research was conducted with a non-equivalent control group design using a sample of 72 students divided into a control group and an experimental group. The instrument used in this study was a test of students learning outcomes in the form of a written test for student assessment. The test is carried out by giving pretest (Pretest) and posttest (Posttest) questions that have adjusted to the learning objectives. Based on the study's results, the N-Gain Value found in the experimental class was higher than in the control class, with values of 0.82 and 0.70 respectively. From the results of the t-test using the Microsoft Excel application, tcount is 2.47, and the ttable with a significance level of 0.05 is 1.99, so tcount value is greater than ttablevalue. So can be concluded that using the flipped classroom learning system based on guided inquiry on buffer materials effective improves student learning outcomes